The Effect of Audit Tenure, Audit Committee, Return on Assets (ROA), and Firm Size on Audit Delay in Banking Companies Listed on the Indonesia Stock Exchange During the 2021–2024 Period - Tiosulistia Tiosulistia; Deasy Arisandy Aruan; Nurganda Siregar (Journal of Economics and Business (JECOMBI), 2026)
Thi Delays in the submission of audited financial reports (Audit Delay) remain a common problem for banking companies listed on the Indonesia Stock Exchange (IDX). Audit delay can reduce the relevance of financial information and influence investor and stakeholder decision-making. This study aims to analyze the effect of Audit Tenure, Audit Committee, Return on Assets (ROA), and Company Size on Audit Delay in banking companies listed on the IDX. This study uses secondary data in the form of annual financial reports of banking companies for the 2021–2024 period. The analysis method used is analysis multiple linear regression with partial and simultaneous testing. The results show that audit tenure, partially, has no significant effect on audit delay. Meanwhile, the Audit Committee, ROA, and company size have a significant effect on audit delay. ROA and company size have a negative effect, indicating that the higher the level of profitability and the larger the company size, the shorter the audit delay tends to be. Simultaneously, audit tenure, audit committee, ROA, and company size have a significant effect on audit delay.s study examines the effect of halal tourism development on economic growth in North Sumatra during the 2020–2025 period. Halal tourism development is represented by the growth of halal certification and the accommodation and food service sector, while economic growth is measured using the growth rate of Gross Regional Domestic Product at constant prices. The study employed a quantitative descriptive-associative design using secondary data from 33 regencies and municipalities, resulting in 198 observations. Data obtained from Statistics Indonesia and the Halal Product Assurance Organising Agency were analysed using SPSS through multiple linear regression, partial and simultaneous tests, and the coefficient of determination. The findings indicate that halal certification growth and the growth of the accommodation and food service sector have positive and statistically significant effects on economic growth. Simultaneously, both variables significantly influence regional economic growth and explain 64.3% of its variation. These findings highlight the importance of strengthening halal certification and tourism-supporting services to promote regional economic development.